The Future of Environmental Law and Complexities of Scale: Federalism Experiments with Climate Change Under the Clean Air Act - Hari M. Osofsky (Washington University Journal of Law & Policy, 2010)
Since its inception, the Clean Air Act ("CAA") has served as an experiment in environmental governance models. As importantly, the CAA has had to be flexible in responding to our evolving understandings of environmental problems. Whether through amendments or new regulatory regimes under existing provisions, the statute has served as a key mechanism in the U.S. federal government's efforts to respond to complex environmental challenges. This Article focuses on the CAA's efforts to grapple with complexities of regulatory scale as an illustration of the new directions in environmental law that are the focus of this symposium. Air moves around over time, which interconnects the local with the international and the past with the future. This Article uses the example of disputes over CAA regulation of motor vehicles' greenhouse gas emissions to illustrate how multiscalar clean air regulation should evolve in light of the changing demands for environmental law outlined by Professor Tarlock in the Introduction to this symposium. It argues that for environmental problems that cross-cut levels of governance, flexible coordination and conflict mechanisms are critical. Future efforts at clean air regulation, whether through the CAA or additional statutes and other governance mechanisms, should incorporate what I have elsewhere termed "diagonal" regulatory thinking. Such approaches bring together multiple actors within (the horizontal) and across (the vertical) levels of government to create innovative governance strategies. Part I introduces the ways in which the CAA grapples with issues of regulatory scale. Part II provides an overview of the two disputes and their resolution under the Obama Administration, with particular attention to the scalar dynamics represented at each stage. Part III considers the broader policy and conceptual questions raised by these disputes for clean air regulation. Part IV concludes by exploring future possibilities for legal and policy approaches to multiscalar clean air regulation.
Keywords: Environmental law; Federal government; Global warming; Environmentalism; United States. Environmental Protection Agency; United States. Clean Air Act; Air pollution control; Emissions trading; Federalism